The effect of video based mobile learning on students’ writing skill - Bandung, A.; Siregar, A.; Siraj, Saedah; Hashim Ali, S.A. (2011)
Mobile learning is the acquisition of any knowledge or skill in the process of learning and teaching through accessing communications and multimedia, such as video, as the main tool and mobile technologies can be used anywhere, anytime. Mobile technology has helped the activity of teaching, especially the teaching of English in secondary schools. It has facilitated learning and accelerated acceptance by students. A study conducted to find out the effects of video-based mobile learning on students’ writing skills in Indonesia examined limits on content and mechanics in writing based on a module used in the English book at Grade 10. The participants of the study comprised 80 students. The data were analyzed using descriptive and inferential statistics including means, standard deviations and t-tests. The video based mobile learning activity conducted has supported teachers in encouraging students to use higher-order thinking skills to solve problems that are relevant to their daily lives. It has allowed students to assess themselves, and they were able to share their learning in the home through mobile learning.